Covid-19 with Methicillin-Resistant Staphylococcus Aureus: Based on Two Cases in Diponegoro National Hospital - Dwi Retnoningrum; Setyo Gundi Pramudo; Taufik Eko Nugroho; Qonita Nur Qolby (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2023)
Background: Coronavirus disease 19 (COVID-19) has become pandemic in the world with a board spectrum of clinical presentation. Secondary infection of methicillin-resistant staphylococcus aureus (MRSA) affects morbidity and mortality in patients with COVID-19.Case: We reported two COVID-19 patients with MRSA hospitalized in intensive care unit (ICU) of Diponegoro National Hospital. The first patient was 61-year-old woman that was referred from another hospital with confirmed COVID-19 infection and acute respiratory distress syndrome and had been intubated. Diabetes mellitus and hypertension were known as comorbid. On day 4 of treatment in ICU, blood culture results showed MRSA infection and antibiotic therapy was replaced with Vancomycin. The patient had clinical improvement and was discharge from the hospital on the 36th day of treatment. The second one was 51-year-old woman admitted with probable COVID-19, type II Diabetes Mellitus and hypertension. On day 9th the patient was transferred to ICU because of respiratory failure, blood culture on day 15th show a result of MRSA and antibiotic therapy was replaced with vancomycin. She declined intubation procedures and died on day 20.Discussion: Antibiotic resistance has become one of the important things in infection management in the world. Multidrug-resistant bacteria (MDR) cause treatment failure which increases the risk of death and cost. MRSA has become one of the most important MDR bacteria during the last decade causing severe infections in health facilities. Complications of bacterial infection in COVID-19, especially bacteremia increases the severity and mortality of severe patients.Conclusion: Coinfection of MRSA in COVID-19 patients can affect the clinical outcome. One of important risk factor is history or prolonged hospitalized. Other factors are comorbidity of the patient and appropriate therapy is needed to reduce mortality in Intensive Care Unit.